Coupling of sorption and deformation in soft nanoporous polymers: Molecular simulation and poromechanics. (April 2020) - Chen, Mingyang; Coasne, Benoit; Derome, Dominique; Carmeliet, Jan
Highlights: Coupling mechanism of sorption and deformation is reviewed by molecular simulations. Poromechanics model is developed based on the coupling mechanism at nanoscale. Different types of sorption isotherms exhibited by different adsorbent-adsorbate systems are quantitatively explained by the developed model. Influences of material properties on the coupled behavior of sorption and deformation are characterized. Abstract: The coupling of water sorption and deformation in soft nanoporous polymers is studied by means of statistical mechanics molecular simulation and the general framework of poromechanics. It is shown that the large amount of water adsorbed by soft nanoporous polymers under free swelling condition results from sorption-induced deformation, which generates more inter-chain space to accommodate water molecules. A poromechanical model is proposed to describe this coupled behavior from the molecular simulation data without any arbitrary fitting. More in detail, by taking into account the mechanical properties, sorption characteristics and structural information as a function of water loading, the model agrees with the molecular simulation and accurately captures the coupling mechanism. Using this model, it is also shown that distinct sorption and deformation behaviors can be observed depending on the material properties. On the one hand, small mechanical modulus, strong adsorbent-adsorbate interaction and significant coupling between sorption/deformation lead to Type II sorption isotherms (with larger sorption amount and sorption-induced deformation). On the other hand, Type I sorption isotherms with limited sorption amount and sorption-induced deformation are obtained for materials with opposite properties.